교복셔츠 개발을 위한 고등학교 남학생의 상반신 체형 연구 - 차수정(Su-Joung Cha); 위혜정(Hye-Jung Wee) (한국컴퓨터정보학회논문지, 2020)
본 연구는 사이즈코리아의 제7차 인체치수조사 자료 중 16-18세 고등학교 남학생 데이터를 사용하여 맞음새가 우수한 교복 셔츠를 개발하기 위하여 상반신 관련 치수를 분석하여 상반신 체형을 분류하고 체형유형별 특성을 파악하고자 하였다. 이를 통해 교복셔츠 개발에 필요한 기초자료를 얻고자 하였다. 자료분석에는 SPSS Ver. 26.0 프로그램을 사용하였다. 고등학교 남학생은 높이항목은 연령별로 유의미한 차이가 없었으나 너비, 두께, 길이, 둘레, 어깨경사각, 몸무게 항목에서는 연령별로유의미한 차이가 나타났다. 상반신 체형은 어깨길이가 길고 상반신 둘레와 너비가 작은 ‘긴 어깨 마른 체형’, 상반신길이가 길고 상반신 둘레와 너비가 큰 ‘긴 상체 비만 체형’, 어깨길이가 짧고 상반신두께와 너비가 중간인 짧은 어깨 보통 체형, 어깨길이가 길고 둘레와 너비는 중간 정도인 ‘긴 어깨보통 체형’ 등 4개로 유형화되었다. 본 연구를 통해 추출된 사이즈 자료를 바탕으로 패턴 개발 및 사이즈 체계 구축을 통해 실질적인 맞음새가 우수한 교복 셔츠 개발이 필요할 것으로 생각된다. The purpose of this study was to development a uniform shirt for high school boys aged 16-18 in the 7th Human Dimension Survey data of Size Korea. The upper body was analyzed to classify the upper body shape and to understand the characteristics of the body by type. Through this, we wanted to obtain the basic data necessary for the development of school uniform shirts. For data analysis, SPSS Ver. 26.0 program was used. In high school boys, there was no significant difference in height by age, but in width, thickness, length, circumference, shoulder slope, and weight, there were significant differences by age. The upper body types were categorized into four types: long shoulder skinny type, long upper body obese type, short shoulder normal type, and long shoulder normal type. Based on the size and body type data extracted from this study, it is thought that the development of uniform shirts with excellent fit should be realized through practical fashion development and construction of a size system. KCI Citation Count: 0